Experimental Tests of Nutrient Limitation in Freshwater Picoplankton - Wehr, John D. (1989)
On the basis of correlative studies, picoplankton in Calder Lake, New York, are apparently unaffected by seasonal fluxes in nutrient (N and P) levels. In this small eutrophic lake, picoplankton (<2.0- to 0.2-μm size) and nanoplankton (<20 to >2 μm) predominate. Microplankton (>20 μm) are typically least important. Experiments were conducted in situ to test whether N, P or N/P ratios affect the predominance of these smaller organisms. Manipulations were run in 4-liter microcosms during June, July, and August 1988, corresponding to periods of increasing stratification and nutrient depletion. Following nutrient additions, phytoplankton were harvested and fractionated into three size classes. Microplankton and nanoplankton were significantly stimulated by both N (2.5 to 50 μM) and P (1 to 20 μM) additions. The severity of nutrient limitation was greatest during July. Picoplankton responded less strongly to N additions and were never P limited. These field data support laboratory studies which indicate that bacterium-sized phytoplankton use nutrients more efficiently and are superior competitors within mixed communities.